Strategi Green Marketing Strategi Green Marketing: Upaya UMKM Memasuki Pasar Internasional - Putra, Bagus Rifky Wahyu; Sugiono, Arif; Aprilia, Hani Damayanti (Jurnal Kompetitif Bisnis, 2024)
This research aims to examine the implementation of strategies in entering the international market. It adopts a descriptive qualitative research approach and employs interactive data analysis. The research focuses on the implementation of strategies (programs, budgets, and procedures) in the steps taken by SMEs to enter the international market (segmentation process, marketing research process, and criteria for selecting strategies). The findings indicate that Kahut Sigerbori as SMEs has achieved success in implementing key strategies (programs, budgets, and procedures) that integrate environmental aspects, particularly focusing on green products, environmentally responsive pricing, educational promotion, waste management, and adapting production to meet international consumer demands. This reflects a strong commitment to sustainability and innovation to enter and sustain in the global market. Recommendations for future research include the utilization of different theories orthe enrichment of other aspects for sustainable research, as well as employing different research methods to provide a broader perspective.